Kierkegaard's Writings, XV, Volume 15 : Upbuilding Discourses in Various Spirits - Kierkegaard, Soren, 1813-1855 (Book collections on Project MUSE., 1993)
In his praise for Part I of Upbuilding Discourses in Various Spirits, the eminent Kierkegaard scholar Eduard Geismar said, "I am of the opinion that nothing of what he has written is to such a degree before the face of God. Anyone who really wants to understand Kierkegaard does well to begin with it." These discourses, composed after Kierkegaard had initially intended to end his public writing career, constitute the first work of his "second authorship." Characterized by Kierkegaard as ethical-ironic, Part One, on the theme of "Purity of Heart Is to Will One Thing," offers a penetrating discussion of double-mindedness and ethical integrity; the irony lies in the relation between factuality and ideality. Part Two, "What We Learn from the Lilies in the Field and from the Birds of the Air," is humorous for Kierkegaard in that it exposes an inverted qualitative difference between the learner and the teacher. In Part Three, "The Gospel of Sufferings, Christian Discourses," the philosopher explores the theme of joy, as in "The Joy of It That the School of Sufferings Educates for Eternity."